Rotasi Varimax dan Median Hirarki Cluster Pada Program Raskin di Kabupaten Lombok Barat - Komalasari, Desy (Jurnal Matematika; Vol 5 No 1 (2015), 2015)
The granting rice program for poor households (Raskin) is one of the West Lombok regency government programs for village poverty. The effectiveness of the program relating to 14 criteria for the poor households Raskin recipients (RTS-PM). The 14 criteria have been grouped into several factors using varimax rotation factor analysis, while the RTS-PM have been grouped using hierarchical median cluster analysis. Four factors obtained based on the analysis. First factor was the house existence, the second factor was the financial ability, the third factor was the house existing facilities, and the four factor was the education of the household head and the purchasing power of clothing. The clustering results using hierarchical median cluster analysis formed 3 clusters. The first cluster contains the RTS-PM which have been grouped into first factor; the second cluster contains the RTS-PM which have been grouped into second and third factor; and the third cluster contains the RTS-PM which have been grouped into fourth factor.
Keywords: Factor Analysis; Varimax Rotation; Hierarchical Median Cluster; Raskin Program